1999
DOI: 10.1046/j.1471-4159.1999.0722047.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate Hypothermia on Constitutive and Inducible Nitric Oxide Synthase Activities After Traumatic Brain Injury in the Rat

Abstract: Abstract:We investigated the effects of therapeutic hypothermia (30°C) on alterations in constitutive (cNOS) and inducible (iNOS) nitric oxide synthase activities following traumatic brain injury (TSI). Male Sprague-Dawley rats were anesthetized with 0.5% halothane and underwent moderate (1.8-2.2 atm) parasagittal fluid-percussion (F-P) brain injury. In normothermic rats (37°C) the enzymatic activity of cNOS was significantly increased at 5 min within the injured cerebral cortex compared with contralateral val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Experimental studies of post-traumatic hypothermia suggest a multitude of possible mechanisms for neuroprotection. These include reducing levels of the excitatory amino acid glutamate; decreasing abnormal blood-brain barrier permeability after traumatic and ischemic insults; inhibiting diffuse axonal injury; reducing proinflammatory cytokines interleukin 1-b and tumor necrosis factor-a; inhibiting apoptotic cell death by decreasing both cytochrome c release from dysfunctional mitochondria as well as levels of caspase, a significant initiator of apoptosis [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Additionally, TBI is often characterized by a postinjury catecholamine surge that correlates directly with the severity of brain injury [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies of post-traumatic hypothermia suggest a multitude of possible mechanisms for neuroprotection. These include reducing levels of the excitatory amino acid glutamate; decreasing abnormal blood-brain barrier permeability after traumatic and ischemic insults; inhibiting diffuse axonal injury; reducing proinflammatory cytokines interleukin 1-b and tumor necrosis factor-a; inhibiting apoptotic cell death by decreasing both cytochrome c release from dysfunctional mitochondria as well as levels of caspase, a significant initiator of apoptosis [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Additionally, TBI is often characterized by a postinjury catecholamine surge that correlates directly with the severity of brain injury [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the selective serotonin reuptake inhibitor sertraline protects against transient global ischemia-induced behavioral despair, and these beneficial effects are reversed by NO upregulation [97]. Hypothermia therapy also inhibits NO production during cerebral ischemia and upregulation of inducible nitric oxide synthase (iNOS), which might account, at least in part, for the neuroprotective effects of this treatment [98, 99]. In short, it appears that NO activation of the GC-PKG pathway may be deleterious, particularly when it leads to induction of iNOS, and some or most of these deleterious effects may be due to NO itself or its peroxide byproducts driven by iNOS.…”
Section: Role Of Cgmp-pdes and Tbimentioning
confidence: 99%
“…The current strategies to treat brain trauma patients are predominantly supportive by decreasing intracranial pressure, providing airway ventilation or resuscitation, and stabilizing cardiovascular function. Hypothermia has also been used in patients with severe traumatic brain injury (TBI) to control refractory elevated intracranial pressure (Smrcka et al, 2005) and to limit the biochemical cascade that may lead to a secondary brain injury (Chatzipanteli et al, 1999). Numerous pre-clinical studies have shown that induced hypothermia is neuroprotective to improve outcomes after traumatic or ischemic brain injury in animal models by limiting the extent of brain injury and improving neurological and functional recovery (Barone et al, 1997).…”
Section: Introductionmentioning
confidence: 99%